ICH M10-Based Validation of a Novel Chromogenic Bioanalytical Method for Quantifying Hesperidin in Biological Samples - Sri, Khagga Bhavya; Pravallika, Jinkala; Sumakanth, Mogili (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: A Chromogenic bioanalytical approach had been developed as well validated for the assessment of specific compound hesperidin in accordance with the ICH M10 guidelines. 2,6-Dichloro quinone 4-chloro imide chromogenic reagent was used to develop the chromogenic method in the visible region. Materials and Methods: When the phenolic group in hesperidin reacts with Gibb's reagent at alkaline medium NaOH solution pH 9, a nucleophilic aromatic substitution reaction takes place, resulting in a blue-coloured product. For this, an ELICO SL-210 UV-visible spectrophotometer was used. A protein precipitation technique using methanol as a precipitating agent was utilized for extracting the compound from human blood plasma. The performance of the method was evaluated by calculating a number of validation parameters including matrix effect, calibration curve, accuracy, precision, Reinjection reproducibility and benchtop stability studies. Results: Both Chromogenic Visible region and UV region bioanalytical methods for hesperidin were validated with r2>0.999 within the range of concentrations 5-35 μg/ mL at 613 nm and 20-140 μg/mL at 285 nm was linearly well-demonstrated for both methods, within and between-run precisions were found to be in limits <15%. These analytes had extraction recoveries of 98.91% and 98.14%. Conclusion: Results showed that the approach was exact, accurate, and is convenient to use for therapeutic drug monitoring and pharmacokinetic studies because it is very quick and accurate in determining the amount of hesperidin in human plasma.
Keywords: 2; 6-Dichloro quinone 4-chloro imide; M10 ICH guidelines; Method validation; Protein Precipitation